Kink Instability of Flux Ropes in Partially Ionized Plasmas - Giulia Murtas; Andrew Hillier; Ben Snow (The Astrophysical Journal)
In the solar atmosphere, flux ropes are subject to current-driven instabilities that are crucial in driving plasma eruptions, ejections, and heating. A typical ideal magnetohydrodynamics instability developing in flux ropes is the helical kink, which twists the flux rope axis. The growth of this instability can trigger magnetic reconnection, which can explain the formation of chromospheric jets and spicules, but its development has never been investigated in a partially ionized plasma (PIP). Here, we study the kink instability in PIP to understand how it develops in the solar chromosphere, where it is affected by charge-neutral interactions. Partial ionization speeds up the onset of the nonlinear phase of the instability, as the plasma β of the isolated plasma is smaller than the total plasma β of the bulk. The distribution of the released magnetic energy changes in fully ionized plasma and PIP, with a larger increase in internal energy associated with the PIP cases. The temperature in PIP increases faster also due to heating terms from the two-fluid dynamics. PIP effects trigger kink instability on shorter time scales, which is reflected in more explosive chromospheric flux rope dynamics. These results are crucial to understanding the dynamics of small-scale chromospheric structures—minifilament eruptions—that thus far have been largely neglected but could significantly contribute to chromospheric heating and jet formation.